Manuais pedagógicos e programas de ensino: interpretações da Escola Nova sobre a prática de ensino na formação de professores (1946-1961) - Bueno, Manuela Priscila de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study intends to contribute to the understanding of the circulation movement of the New School ideas in the state of São Paulo, between 1946 and 1961, considered by historiography as a period of consolidation of the New School guidelines on the regulatory framework of laws and decrees. To this end, we will take as a research source educational guidelines contained in the syllabus published by decrees of the State Department of Education and teaching manuals produced for use in training courses for primary school teachers, for the discipline of Teaching / Methodology Practice and Practice of Primary Education. Understanding them as devices mediators between legislative norms and teaching practice. These sources make up a repertoire of professional knowledge therefore regulated by the doctrinal field prescribe ways to make them feasible. In order to make the analysis in light of the theoretical and methodological framework of cultural history, which provides the basis for thinking about social and pedagogical practices as important components of theoretical concepts and how consolidating elements of outstanding ideas. The analysis is based on the plan for the course of teacher education published in 1953, 1954, 1958 and 1960 and in textbooks Teaching Practice Notions (1951) and Methodology of Primary Education (1952), of Theobaldo Miranda Santos, and Summary General Teaching (1957), Luiz Alves de Mattos. Such sources allow the understanding of different appropriations through which the pedagogical renewal was put into circulation, established practices continuities and contributed to the incorporation of knowledge to the school culture

O presente estudo intenta contribuir para a compreensão do movimento de circulação das ideias da Escola Nova, no estado de São Paulo, entre os anos de 1946 e 1961, considerado pela historiografia como período de consolidação das diretrizes escolanovistas no âmbito normativo de leis e decretos. Para tanto, tomaremos como fonte de pesquisa as diretrizes educacionais contidas nos programas de ensino, publicados através de portarias da Secretaria de Estado da Educação e manuais pedagógicos produzidos para uso nos cursos de formação de professores primários, destinados à disciplina de Prática de Ensino/Metodologia e Prática do Ensino Primário. Entendendo-os como dispositivos mediadores entre as normas legislativas e a prática docente. Essas fontes configuram um repertório de conhecimentos profissionais, pois, reguladas pelo campo doutrinário prescrevem modos para torná-los praticáveis. Pretende-se fazer a análise sob a luz do referencial teórico-metodológico da História Cultural, que proporciona o embasamento para pensar as práticas sociais e pedagógicas como componentes importantes das concepções teóricas e como elementos de consolidação das ideias em circulação. A análise está baseada nos programas de ensino para o curso de formação de professores publicados em 1953, 1954, 1958 e 1960 e nos manuais didáticos Noções de Prática de Ensino (1951) e Metodologia do Ensino Primário (1952), de Theobaldo Miranda Santos, e Sumário de Didática Geral (1957), de Luiz Alves de Mattos. Tais fontes permitem a compreensão de diferentes apropriações por meio das quais a renovação pedagógica foi posta em circulação, estabeleceu continuidades práticas e contribuiu para a incorporação de saberes à cultura escolar
Keywords: Education; Educação; Escola nova; Professores - Formação; Pratica de ensino; São Paulo (Estado) - 1946-1961